A Novel Music Recommendation Method Combining Music Sub-Personality and Social Network Behavior Analysis - Chunhua Ju; Zhiyi Huang; Fuguang Bao (Dianxin kexue)
In order to recommend music conforming to the people’s sentiment state in real time，a novel music recommendation method combining music sub-personality and social network behavior analysis was proposed.Through sentiment analysis of the users’ words and sentences which was released on Weibo and other social network，the method calculated the users’ music preference in a sentiment state，the most suitable music was recommend to users in that sentiment state.Experimental results show that the proposed method can alleviate the effect of user data sparsity on the recommendation results.